2017
DOI: 10.1111/imb.12340
|View full text |Cite
|
Sign up to set email alerts
|

The roles of mucus‐forming mucins, peritrophins and peritrophins with mucin domains in the insect midgut

Abstract: Most insects have a gut lined with a peritrophic membrane (PM) consisting of chitin and proteins, mainly peritrophins that have chitin-binding domains. The PM is proposed to originate from mucus-forming mucins (Mf-mucins), which acquired a chitin-binding domain that interlocked with chitin, replacing mucus in function. We evaluated the expression of Mf-mucins and peritrophins by RNAsequencing (RNA-seq) throughout the midgut of four distantly related insects. Mf-mucins were identified as proteins with high o-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 66 publications
(114 reference statements)
0
41
0
1
Order By: Relevance
“…Previous studies have shown that the origin and function of the PM in the Chinese mitten crab may be very different from that in insects (Huang et al, ; Li, Cai, et al, ). For example, the PM lines the midgut epithelium in insects (Dias et al, ). However, in the Chinese mitten crab, the PM has been observed in the stomach and hindgut but was not obvious in the midgut under a microscope (Li, Cai, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the origin and function of the PM in the Chinese mitten crab may be very different from that in insects (Huang et al, ; Li, Cai, et al, ). For example, the PM lines the midgut epithelium in insects (Dias et al, ). However, in the Chinese mitten crab, the PM has been observed in the stomach and hindgut but was not obvious in the midgut under a microscope (Li, Cai, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The PM is composed of proteins (peritrophins) that are interlocked with chitin fibrils that are associated with other proteins (Dias et al, 2018;Tellam, Wijffels, & Willadsen, 1999). Peritrophins account for approximately 35%-55% of the total mass of the PM in many insects, and the sizes or molecular weights of these proteins vary greatly (Elvin et al, 1996;Hu et al, 2012;Wang & Granados, 2010).…”
mentioning
confidence: 99%
“…For trypsins, the largest numbers of gene copies are observed in the genomes of species from the Noctuidae (28 to 42), Plutellidae (37), and Sphingidae (35) moth families (Tables S1,S2). The number of genes encoding chymotrypsins is highest in the genomes of species from the moth families Plutellidae (71) and Noctuidae (32 to 58) and the butterfly family Pieridae (61) ( Tables S3,S4).…”
Section: Lepidopteran Trypsin and Chymotrypsin Gene Evolutionmentioning
confidence: 99%
“…Reproduced from (Smith et al 2015) of food into the digestive cavity/tract and to expel undigestible material and feces. Mucous also protects the digestive epithelium from harmful molecules, such as digestive enzymes, and microorganisms (Bakshani et al 2018;Dias et al 2018;Liévin-Le Moal and Servin 2006). Mucocytes have not been reported in adult Porifera, but mucous-secreting cells are present in larval sponges (Homoscleromorpha-Ereskovsky et al 2007; Demospongiae- Leys and Degnan 2001).…”
Section: Mucous Cellsmentioning
confidence: 99%